Pengaruh Pembelajaran Guided Inquiry Disertai Jurnal Belajar terhadap Kemampuan Berpikir Kritis Siswa pada Pelajaran Biologi Kelas XI SMA - Wulandari, Desy; Maridi, Maridi; Probosari, Riezky Maya (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The purpose of this research is to know the influence of Guided Inquiry learning  with a learning journal on students’ critical thinking skills. The research was considered as quasi experiment research using Nonrandomized Control Group design with Pretest-Posttest. Sampling technique using purposive sampling. The study population is all students of class XI IPA SMA N 1 Karanganyar Academic Year 2017/2018 consisting of eight classes. Sample of class consists of two classes, eksperiment class with Guided Inquiry learning with learning journal and control class with Guided Inquiry learning. Data collection techniques use essays test, observations, and documentation. The normality test with Kormogorov-Smirnov test and homogeneity with Leneve test. Hypothesis test used is Independent t test with 5% (α= 0.05) significance level assisted with SPSS 22. The research procedure includes planning, implementation and data analysis.The conclusion of this research show that  the application of Guided Inquiry learning with learning journal has given effect towards student’s critical thinking skill.